Rose-Tinted Videogames - Ember Martin (Press Start)
Nostalgia is a common experience, with videogames providing a strong potential trigger for nostalgic feelings towards the playing of games or memories about games. Nostalgia has positive effects on creativity, inspiration, exploration, social connectedness, and a sense of self-continuity. These elements find a natural home in the creative industries and have led to the creation of a multitude of nostalgic products. This study investigates nostalgia’s influential role in videogame development, analysing how nostalgia-driven decisions made by developers are interpreted by players who share a nostalgic object. This paper examines three case study games based on three lenses: Remind, Repeat, and Revive. These categories and cases demonstrate practical development insight into core design decisions and player reception. For developers, these findings could lead to the accurate representation and sensitive implementation of nostalgic objects in games. Players could enhance their enjoyment of games by learning to identify where idealised recollections diverge from the subjective and objective reality of their nostalgic object.